Lelang Pengadaan Barang dan Jasa Sinyal Telekomunikasi Dari Stasiun Araskabu Menuju Bandara Kualanamu Oleh Executive Vice President Pt. Kereta Api Indonesia (Persero) dengan Bajatra (Analisis Putusan Nomor 181 Pk/Tun/2016) - Alam syah putra (Jurnal Perspektif Hukum, 2022)
The user party is the party who requests or assigns the provider a task to supply or manufacture goods or make certain jobs. The problem in this research is the legal regulation of the auction of the procurement of goods and services in government regulations. Sanctions that can be imposed on parties related to the procurement of government goods/services that do not meet the requirements of the provisions of the work order. How is the judge's legal considerations in deciding the dispute between PT. Kereta Api Indonesia (Persero) with Bajatra in Decision Number 181 PK/TUN/2016. This research uses normative legal research methods. Presidential Regulation Number 16 of 2018 concerning the Procurement of Government Goods/Services provides guidelines for regulating and implementing the procurement of goods/services that accommodates the development of government needs regarding the regulation of the procurement of goods/services in order to fulfill the maximum benefit value and be able to contribute in increasing the use of products. domestic. Sanctions that can be imposed on parties related to the procurement of government goods/services that do not meet the requirements of the provisions of the work order. The sanctions are regulated in Article 83 of Presidential Regulation Number 16 of 2018, one of which is in the form of sanctions for inclusion in the Black List. The judge's legal considerations in deciding the dispute between PT. Kereta Api Indonesia (Persero) With PT. Bajatra in Decision Number 181 PK/TUN/2016 is a test of the validity of both procedural and substantial terms of the imposition of a blacklist addressed to the Plaintiff issued by the Defendant, not regarding the provision of goods and services in terms of telecommunication signal work from Araskabu station to Medan Kualanamu Airport. and Sepur 8, 9 Medan Station Emplacement. Implementation of the work agreement between PT. Bajatra and PT. KAI.